The compatibility of concurrent high intensity interval training and resistance training for muscular strength and hypertrophy: a systematic review and meta-analysis - Sabag, A.; Najafi, A.; Michael, S.; Esgin, T.; Halaki, M.; Hackett, D. (Journal of Sports Sciences, 2018)
The purpose of this systematic review and meta-analysis is to assess the effect of concurrent high intensity interval training (HIIT) and resistance training (RT) on strength and hypertrophy. Five electronic databases were searched using terms related to HIIT, RT, and concurrent training. Effect size (ES), calculated as standardised differences in the means, were used to examine the effect of concurrent HIIT and RT compared to RT alone on muscle strength and hypertrophy. Sub-analyses were performed to assess region-specific strength and hypertrophy, HIIT modality (cycling versus running), and inter-modal rest responses. Compared to RT alone, concurrent HIIT and RT led to similar changes in muscle hypertrophy and upper body strength. Concurrent HIIT and RT resulted in a lower increase in lower body strength compared to RT alone (ES = -0.248, p = 0.049). Sub analyses showed a trend for lower body strength to be negatively affected by cycling HIIT (ES = -0.377, p = 0.074) and not running (ES = -0.176, p = 0.261). Data suggests concurrent HIIT and RT does not negatively impact hypertrophy or upper body strength, and that any possible negative effect on lower body strength may be ameliorated by incorporating running based HIIT and longer inter-modal rest periods.